Development and consequences of financial globalization - Palomo Garrido, Aleksandro (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The globalization process managed to open new spaces that favored the financial and economic expansion. This financial expansion resulted in economic growth during the nineties. The accumulated surplus capital, which were threatened by the depreciation, found opportunities for profitable investment in the expansion of the globalization process. However, it also had unintended consequences such as distortion of the economic system through an excessive financialization.
Keywords: globalization; the globalization process; financial globalization; financialization